Toward a cure for HIV—Seeking effective therapeutic vaccine strategies. Issue 12 (December 2015) - Autran, Brigitte
Abstract : This review article focuses on the rationale and evaluation of therapeutic vaccines against HIV. This strategy has been developed in order to restore or restimulate HIV‐specific immunity in patients treated with antiretroviral therapies. Despite the lack of good candidate vaccines against HIV, two objectives have been targeted during the past 15 years. Therapeutic immunization was first proposed to help control virus relapses during treatment interruptions. More recently, the concept of therapeutic immunization has been boosted by efforts to reach HIV remission or cure, in combination to HIV reactivating agents, to help purge HIV reservoirs in a "shock and kill" strategy. This review analyses the rationales for these strategies and the results of the most widely therapeutic vaccines designed to generate T‐cell immunity, i.e. recombinant viral vectors and dendritic cell‐based strategies, while extremely few strategies targeted HIV‐specific Abs. Only marginal control of HIV was obtained with cellular‐based strategies, suggesting that approaches targeting or using broadly neutralizing Abs, should be of benefit for future efforts of therapeutic immunization against HIV in the quest toward a cure for HIV.